Islamic Tenets and Values in Laila Lalami’s The Other Americans - Febrina, Fitri (UIN Syarif Hidayatullah Jakarta, 2022)
After 9/11, the stereotypes and generalizations against Muslims are exacerbated. By examining Lalami’s The Other Americans, this paper aims to challenge the prejudice and orientalist perceptions towards Muslims and US-Muslims through the aesthetic strategies that the author uses: Islamic tenets and values. The method used for this analysis is a Critical Textual Analysis and engages with Postcolonial Studies, particularly Edward Said's concept of the Othering. The analysis found that prejudicial perception is a challenge through Islamic tenets such as the practice of Qur'an recital and fasting (sawm) which promotes Islam as consolation and peace. The novel also challenges the image of savagery and backwardness in the orientalist views through Islamic values that reflect the qualities of the Prophet Muhammad by depicting the values of perseverance (istiqamah), compassion, and innovation through embracing entrepreneurship. The findings reveal that the prejudiced views of Islam that are maintained by insularity and ignorance are countered by the Islamic tenets and values that are promoted in Islam and practiced by its believers. Thus, Lalami’s novel undermines anti-Muslim racism by exploring Islamic tenets and values, including the Quran and hadiths, practiced by Lalami’s characters who have suffered from the exclusion of U.S. belonging for centuries.